Discovering and Using Design Patterns in the WWW - Lyardet, Fernando Daniel (1999)
In this paper, we discuss how the idea of design patterns can be used in the context of the World Wide Web, for both designing and implementing web sites or more complex information systems. We first motivate our work by discussing which are the most outstanding problems in designing Web-based information systems. Then we briefly introduce design patterns and show how they are used to record and reuse design information. We next present some simple though powerful design patterns and show known uses in the WWW. Finally, we outline a process for building applications by combining a design methodology (OOHDM) with design patterns.